2021
DOI: 10.3390/ph14040319
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Enzyme Membrane Reactor to Intensify the α-O-Glycosylation of Resveratrol Using Cyclodextrins

Abstract: The O-glycosylation of resveratrol increases both its solubility in water and its bioavailability while preventing its oxidation, allowing a more efficient use of this molecule as a bioactive ingredient in pharmaceutical and cosmetic applications. Resveratrol O-glycosides can be obtained by enzymatic reactions. Recent developments have made it possible to selectively obtain resveratrol α-glycosides from the β-cyclodextrin–resveratrol complex in water with a yield of 35%. However, this yield is limited by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…An increase in antibacterial activity and α-glucosidase inhibition were reported for hesperidin glycoside [ 11 ]. The O -glycosylation of resveratrol was reported to increase both its solubility in water and bioavailability while preventing oxidation [ 12 ]. The glycosylation of rutin has been extensively studied and is considered an efficient and available method to increase solubility [ 13 , 14 , 15 ]; however, information on the changes in its properties and efficacy is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in antibacterial activity and α-glucosidase inhibition were reported for hesperidin glycoside [ 11 ]. The O -glycosylation of resveratrol was reported to increase both its solubility in water and bioavailability while preventing oxidation [ 12 ]. The glycosylation of rutin has been extensively studied and is considered an efficient and available method to increase solubility [ 13 , 14 , 15 ]; however, information on the changes in its properties and efficacy is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hesperetin with high Log P value (poorly water soluble) showed high antibacterial activity against the Gram-positive and Gram-negative bacteria tested, but hesperidin glucoside, with very low Log P value (highly water soluble), also showed higher antibacterial activities than hesperidin with high Log P value. Lipophilicity of flavonoids is an important factor for antimicrobial activity, but high lipophilicity does not always lead to high antimicrobial activity in many cases [ 81 , 82 , 83 ]. In this study, 2% of DMSO did not sufficiently increase the solubility of hesperidin or hesperetin, and there were some precipitates in the bacterial culture broth at high concentration of hesperidin or hesperetin.…”
Section: Discussionmentioning
confidence: 99%
“…1) 39 . Research has moved over the past few years toward the synthesis of their αanomeric counterparts whose aqueous solubility and surfactant properties are superior [163][164][165][166] .…”
Section: Implication Of Cyclodextrins For the Green Synthesis Of Stil...mentioning
confidence: 99%
“…The green synthesis of 3-O-α-D-glucosyl resveratrol with sucrose and not CDs as a glucose donor, has already been performed by a combination of an ionic liquid and a buffer, which considerably increases resveratrol solubility under the catalytic action of a phosphorylase from Bifidobacterium adolescentis 167 . Several works have reported achievement of stilbene O-glucosylation with cyclodextrin glucosyl-(glucano)-transferases (CGTases) from various sources as biocatalysts utilizing starch or CDs as glucose donors [163][164][165][166]168,169 (Table 4). CGTases have often been employed for the biosynthesis of various polyphenolic glucoside derivatives: epicatechin glucosides 170 , kaempferol glucoside 171 , genistein diglucoside 172 , flavonol and flavanones glucosides 173 , pinoresinol glucoside 174 or α-arbutin 175 .…”
Section: Implication Of Cyclodextrins For the Green Synthesis Of Stil...mentioning
confidence: 99%
See 1 more Smart Citation